IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI MATA PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN KELAS III SD 2 PADOKAN BANTUL - Novitriyanti Novitriyanti; Trisharsiwi Trisharsiwi; Taryatman Taryatman (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to describe character education through sports and health physical education subjects in grade III SD 2 Padokan Bantul. This study included qualitative descriptive research. The subjects of this study were the principle, sports and health physical education teacher, class III teacher, and class III student. Data collection techniques use observation, interviews, and documentation. Data analysis techniques in the study through data collection, data reduction, data display, dan conclusion drawing/verifying. The result of the research on the implementation of character education through Sports and Health Physical class III SD 2 Padokan Bantul bases are described in the form of descriptions and tables.Â